2009
DOI: 10.1139/o09-049
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hsf1 activity by novobiocin and geldanamycin

Abstract: Since Hsp90 is a known modulator of HSF1 activity, we examined the effects of two pharmacological inhibitors of Hsp90, novobiocin and geldanamycin, on HSF1 DNA-binding activity in the Xenopus oocyte model system. Novobiocin exhibits antiproliferative activity in culture cells and interacts with a C-terminal ATP-binding pocket on Hsp90, inhibiting Hsp90 autophosphorylation. Treatment of oocytes with novobiocin followed by heat shock results in a dose-dependent decrease in HSF1 DNA-binding and transcriptional ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 41 publications
6
59
1
Order By: Relevance
“…Moreover, we have found no clear correlation between the potency of the HSP90 inhibitors and their ability to induce osteoclast formation. It should also be noted that these compounds had a minimal effect on the induction of HSR, consistent with previous observations that novobiocin causes a dose-dependent decrease in Hsf1 DNA-binding and transcriptional activities (61). Combined, these results suggest that HSP90 inhibition per se may not enhance osteoclast formation and is consistent with a role for the involvement of Hsf1 downstream target involvement.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we have found no clear correlation between the potency of the HSP90 inhibitors and their ability to induce osteoclast formation. It should also be noted that these compounds had a minimal effect on the induction of HSR, consistent with previous observations that novobiocin causes a dose-dependent decrease in Hsf1 DNA-binding and transcriptional activities (61). Combined, these results suggest that HSP90 inhibition per se may not enhance osteoclast formation and is consistent with a role for the involvement of Hsf1 downstream target involvement.…”
Section: Discussionsupporting
confidence: 90%
“…This reveals a key mechanistic advantage for the combination, compared to single-agent treatment with N-terminal Hsp90 inhibitors, that may markedly improve patient responses. Similar to combined 17-AAG and bicalutamide, C-terminal targeted Hsp90 inhibitors do not elicit a heat shock response (Conde et al 2009, Eskew et al 2011, and development of these agents is currently being pursued to take advantage of this characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, a double mutant lacking constitutively expressed Hsp90 and a cyclophilin 40 homolog, hsc82⌬ cpr7⌬, exhibits high levels of Hsf1 activity in the absence of stress and is thermotolerant (113,169). Moreover, studies to identify Hsf1 pharmacological modulators showed that some Hsf1 activators also function as Hsp90-specific inhibitors, such as geldanamycin and radicicol (67,241,403). Recently, celastrol, an active component of Chinese medicine, was found to promote HSP gene expression through Hsf1 activation and to block the maturation of Hsp90-dependent steroid receptors in yeast and human cells (185,465,507).…”
Section: Hsf1mentioning
confidence: 99%